1999
DOI: 10.1210/jcem.84.6.5772
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Estrogen Inactivation in Colonic Cancer

Abstract: Age and sex differences in the incidence of colonic cancer, together with epidemiological data on patients taking hormone replacement therapy, suggest the involvement of estrogens. Analogous to the role of aromatase in breast cancer, we postulated that steroid metabolism within the colon itself may be a crucial mechanism in regulating tissue exposure to estrogens. We have characterized expression of aromatase (responsible for converting C19 androgens to C18 estrogens) and 17beta-hydroxysteroid dehydrogenase (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
4
36
0
Order By: Relevance
“…Initial enzyme activity studies revealed a similar pattern of oestrogen metabolism to that previously described in primary colonic mucosae (English et al, 1999). In Caco-2, SW620 and HT-29 cells the predominant 17β-HSD activity was oxidative conversion of E 2 to E 1 .…”
Section: Analysis Of 17β-hsd Activity In Vitrosupporting
confidence: 67%
See 1 more Smart Citation
“…Initial enzyme activity studies revealed a similar pattern of oestrogen metabolism to that previously described in primary colonic mucosae (English et al, 1999). In Caco-2, SW620 and HT-29 cells the predominant 17β-HSD activity was oxidative conversion of E 2 to E 1 .…”
Section: Analysis Of 17β-hsd Activity In Vitrosupporting
confidence: 67%
“…Analogous to well documented studies in breast cancer (O'Neill et al, 1988;Sasano et al, 1996), we have postulated that local steroid metabolism in the colon may play a key role in modulating the effects of oestrogens by determining the tissue availability of active E 2 . In recent studies using tissue biopsies we have shown that the normal colonic mucosa has a high capacity for metabolism of E 2 (English et al, 1999). Furthermore, the predominant metabolic activity, inactivation of E 2 to oestrone (E 1 ), was significantly decreased in paired tumour biopsies.…”
mentioning
confidence: 99%
“…In line with this, English et al 28 reported that oxidative 17HSD activity was significantly lower in colon tumors compared to normal mucosa. Based on Northern analysis, they concluded that the decrease was due mainly to decreased expression of 17HSD type 4, another 17HSD enzyme with oxidative activity.…”
Section: Discussionmentioning
confidence: 62%
“…28,33 Enmark et al, 26 using in situ hybridization, showed that normal human colon cells express ER in the form of ER␤, which is markedly diminished in malignant colon tissues, 34 possibly through a posttranscriptional regulatory mechanism. In line with these results, our study showed that normal colon cells express ER␤ but not ER␣, while no ER subtype was detected in the malignant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation